Calculation and Analysis of Sluice Bottom Seepage with Two Methods. Issue 1 (January 2021) - Jiang, Linlin; Zhao, Chuan; Zhang, Jiongjiong
Abstract: Based on Tianjin Xihe control sluice, this paper uses the improved resistance coefficient method and ABAQUS finite element software to calculate the seepage at the bottom of sluice. By comparing the calculation results, the advantages and disadvantages of two methods to calculate the seepage at the bottom of sluice are analyzed, which provides a new idea for the calculation of sluice bottom seepage.